2022
DOI: 10.3390/f13050639
|View full text |Cite
|
Sign up to set email alerts
|

The Shift from Energy to Water Limitation in Local Canopy Height from Temperate to Tropical Forests in China

Abstract: Canopy height greatly affects the biomass stock, carbon dynamics, and maintenance of biodiversity in forests. Previous research reported that the maximum forest canopy height (Hmax) at global and regional scales could be explained by variations in water or energy availability, that is, the water- or energy-related hypothesis. However, fundamental gaps remain in our understanding of how different drivers (i.e., water and energy) contribute to the Hmax at the local scale. In this study, we selected eight dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Subsequently, it becomes necessary to understand the drivers influencing canopy height and its spatial variation along with the relationships among them. Among the several factors that influence canopy height, various studies have found the hydraulic limitation hypothesis (water availability) and the energy limitation hypothesis (energy in the form of solar radiation or temperature) to be pivotal [6,[8][9][10][11]. At large spatial scales, climatic attributes along with historical conditions have been found to mediate canopy height, whereas at fine scale, it is the site-specific parameters such as topographical variables (elevation, slope, curvature, aspect), soil parameters and local environmental conditions which drive canopy height [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, it becomes necessary to understand the drivers influencing canopy height and its spatial variation along with the relationships among them. Among the several factors that influence canopy height, various studies have found the hydraulic limitation hypothesis (water availability) and the energy limitation hypothesis (energy in the form of solar radiation or temperature) to be pivotal [6,[8][9][10][11]. At large spatial scales, climatic attributes along with historical conditions have been found to mediate canopy height, whereas at fine scale, it is the site-specific parameters such as topographical variables (elevation, slope, curvature, aspect), soil parameters and local environmental conditions which drive canopy height [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…With advances in technology, remotely sensed LiDAR (satellite and airborne) data have been utilized to analyze canopy heights at global and local scales, with a few utilizing LiDAR for investigating the relationship of canopy height with its environmental drivers. Wang et al [11] investigated the relationships between canopy height, water and energy conditions using UAV-based LiDAR point cloud data. They found that the water limitation hypothesis was able to better explain the variance in canopy heights in tropical forests in China, while the same was true for the energy limitation hypothesis in temperate forests [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation